1984
DOI: 10.1097/00000658-198409000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Electron Beam Irradiation for Patients with Unresectable Pancreatic Carcinoma

Abstract: Since 1978 we have used electron beam intraoperative radiation therapy (IORT) to deliver higher radiation doses to pancreatic tumors than are possible with external beam techniques while minimizing the dose to the surrounding normal tissues. Twenty-nine patients with localized, unresectable, pancreatic carcinoma were treated by electron beam IORT in combination with conventional external radiation therapy (XRT). The primary tumor was located in the head of the pancreas in 20 patients, in the head and body in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(32 citation statements)
references
References 10 publications
2
27
1
2
Order By: Relevance
“…Some investigators have attributed some complications of IORT and EBRT. These include episodes of intestinal bleeding, neuropathy, increased infection, and secondary neoplasms [29][30][31][32][33]. We did not show any of these complications in our series.…”
Section: Discussioncontrasting
confidence: 52%
“…Some investigators have attributed some complications of IORT and EBRT. These include episodes of intestinal bleeding, neuropathy, increased infection, and secondary neoplasms [29][30][31][32][33]. We did not show any of these complications in our series.…”
Section: Discussioncontrasting
confidence: 52%
“…Several reports have also indicated the efficacy of IORT + EBRT on local control (5,(15)(16)(17)(18) (17). These results indicate that combined IORT, with or without, EBRT produced better local control for patients with unresectable tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Median survival was reported to be in the range of 13 to 19 months in patients undergoing complete resection with IORT [3,14,15]. Although it has been reported that the combination of IORT and external radiation therapy did not result in any major improvement in overall survival for patients with locally advanced unresectable pancreatic carcinoma [16,17], encouraging results from this combination treatment were reported by Tepper et al [15] and Shipley et al [18], who reported median survivals of 14.0 and 16.5 months, respectively. Significantly improved survival was obtained following surgical bypass plus IORT in stage III patients who had no distant metastasis in our series; and a favorable effect of IORT even in patients with distant metastasis (i.e., stage IV in the TNM classification) was reported by Nishimura et al [19].…”
Section: Discussionmentioning
confidence: 95%